PRODUKSI BAHAN PEMANIS DARI KULIT BUAH CARICA (Carica pubescens) DENGAN METODE HIDROLISIS ASAM - , REFIANTY AMALIA F, Fahrizal Yusuf Affandi, STP, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The production process of wet candied fruit Carica produce byproducts that carica fruit skin that is not harmful but it should be minimized. Carica fruit leather produced UD Yuassa Food Berkah Makmur thought to contain sugars that can be converted into sweeteners. Utilization of Carica fruit skin will greatly help the industry because it can reduce the use of sweeteners with sugar alternatives that glucose production as well as providing a major contribution to environmental melestraikan around the industry. This thesis aims to determine which parts of the stages of the production process generates carica fruit skin, knowing the value of reducing sugar and total sugar produced, and determine variables of concentrated sulfuric acid concentration on the optimal hydrolysis into glucose carica skin. Carica fruit skin reduced in size and added sulfuric acid (H2SO4). Hydrolysis is done by using a variation of 30% concentrated acid concentration